(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aimed to assess the status of cell mediated immunity for pulmonary tuberculosis patients through evaluation levels of Interleukins (IFN-γ ,IL-10, IL-12) and estimation vitamin D3 . Whole blood samples collected from 50 pulmonary tuberculosis patients who are admitted to consultant clinic for respiratory diseases in Hilla – Babylon province during the period from February 2016 to February 2017. Out of the pTB patients, there were 27 males and 23 females, the patients age range was between 12-80 years. Cytokines levels and vitamin D3 estimated by using ELISA technique. The mean of serum concentration of IL-10 and IL-12 revealed that there is a significantly increased (p˂ 0.05) in pulmonary tuberculosis patients as compared to controls (4.024 and 1.049)pg/ml (51.563 and 13.514) pg/ml ,respectively. While, the mean of serum concentration of IFN-γ showed no significant increasing (p˃0.05) in pulmonary tuberculosis patients compared to controls (36.505 and 25.019)pg/ml. The mean of serum concentration of VD3 showed a significant decreasing (p˂ 0.05) in pulmonary tuberculosis patients as compared to controls (18.186 and 29.321) ng/ml. Conclusions: The results provide a good correlation between the levels of IL-10 , IL-12, IFN-γ and Vitamin D3 with the cellular immunity against pulmonary tuberculosis.